Optimization for Biogas Power Plants using Automatic Control of Gas Pressures - Candra, Dodiek Ika; Tamayo, Camilo Andreas Wilches (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2013)
In many cases, gas storages on biogas power plants are not used optimally to store gas as much as their capacity. The digester is sometimes overload to store gas and the controller cannot deliver gas to other storage. Consequently, gas is often released from digester to avoid over pressure. At the end, biogas power plant has less efficiency. Hence, a mechanism to control gas pressure to make different pressure between its storages is required. Fans were used to manipulate the most majority system pressures on a biogas power plant using frequency converters. Measurements, simulations, and experiments were conducted to create a new system on a biogas power plant. A controller, Programmable Logic Controller was used to control the entire system pressure using Proportional-Integral-Derivative algorithm. When the gas pressures are not in the allowable range of pressure, then the controller changes the fans’ frequency to the desired conditions. As a result, gas moves to another storage and system pressures are in the allowable range.